ESTUDO DE CASO EM BAURU, SP: CIDADES SEM LIMITES NA ‘URBANIZAÇÃO GENERALIZADA’ DE HENRI LEFEBVRE (Terr@ Plural, 2019)
Global urban processes also emerge in the mid-sized cities, from their local logics, contributing to the dissolution of the urban/rural binomial. This paper investigates such processes based on a case study about Bauru, a medium-sized city located in the center of São Paulo state. It retakes Henri Lefebvre's idea of "generalized urbanization" and reveals the need to revise public policies and planning in the face of phenomena that do not fit into urban/rural classifications - and thus reveal the spread of an uneven urban fabric and the degradation of natural landscapes.